Remote active monitoring of patients after myocardial infarction: are there any advantages over standard outpatient monitoring? - D. Yu. Sedykh; T. S. Alkhimova; V. V. Kashtalap; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To compare the clinical effectiveness of two patient management programs for 12 months after myocardial infarction (MI) (standard outpatient monitoring and office- based management with additional active remote medical supervision).Material and methods. 150 patients with non-fatal MI aged 35 to 70 years were included. At discharge, patients were randomized into groups with different followup programs for 12 months after MI (standard outpatient follow-up (n=75) or its combination with active remote patient monitoring (n=75)). One year after MI, the following parameters were was assessed: vital status, frequency of emergency cardiovascular hospitalizations due to coronary insufficiency, actual adherence to therapy and regular outpatient follow-up, achieving target parameters of cardiovascular health, and dynamics of behavioral risk factors.Results. In the group of patients with MI who spent 12 months in a combined program, compared with patients with standard monitoring, 4.8 times fewer combined ischemic events were registered (p<0.001); the proportion of emergency hospitalizations for cardiovascular reasons was 4.7 times lower (p<0.001). It was shown that patients observed in a combined program throughout the year were 1.7 times more likely to make regular visits to the clinic (p<0.001). Over a year, patients with active remote monitoring were more likely to achieve behavioral changes: the proportion of patients reporting an increase in weekly physical activity (p=0.013) and a decrease in the number of periods of monthly stress or their complete absence from work and/or home was 1.6 times higher (p=0.020), who were 1.8 times more likely to indicate a decrease in the frequency of monthly alcohol consumption and a decrease in the number of servings (p=0.001), as well as changes in dietary patterns. Patients who underwent additional remote patient monitoring were 1.2 times more likely to indicate a decrease in daily consumption of table salt (p = 0.011), 1.3 times more likely to note the addition of dietary meat to the diet (p=0.003), 1.1 times more likely to more often — fresh and cooked vegetables (>300 g per week) (p=0.032), 1.4 times more often — fresh fruits and berries (>300 g per week) (p=0.003), 1.2 times more often reported about reducing the consumption of complex carbohydrates to > ¼ of the plate per day (p=0.036).Conclusion. An original program of combined standard outpatient monitoring of patients and their active remote monitoring for 12 months after MI demonstrated advantages in secondary prevention of cardiovascular events and modification of cardiovascular risk factors.